(untitled) (Medical Forum Monthly, 2024)
Objectives: To find out a more effective method for teaching anatomy at undergraduate level by comparing PowerPoint and Blackboard-Chalk modes. Study design: Comparative study Place and duration of study: This study was conducted at the departments of anatomy at Army Medical College, Islamic International Dental College, Islamabad Medical and Dental College in Rawalpindi/Islamabad from March to May 2010. Subjects and methods: 130 students who were exposed to both the PowerPoint and Blackboard-Chalk based lectures in three medical and dental colleges, were selected at random from class nominal roll. A specially designed questionnaire was sent to them. 82% (106) of the students returned the survey form with the response. Results: Various advantages and disadvantages of both the PowerPoint and Blackboard-Chalk method were highlighted in the students’ response. 65%, 62% and 60% of the students recommended that a combination based upon Blackboard as main format, and supplemented by PowerPoint should be used in lectures (embryology, histology and gross anatomy), gross anatomy demonstrations and histology practical respectively. The PowerPoint was recommended to be used in the beginning to outline the lecture and summarize the things at the end with picture showing wherever needed.